Lowalangi Deity in Nias Community Traditions Reviewed from the Perspective of Christian Faith - Erwin Zai; Pantjar Simatupang (Global Writing Academica Researching & Publishing, 2023)
Understanding God's name is a sacred thing for Christians, so placing God's name in Christian life gives it different meanings without eliminating its substance. One example is the change of God's name in the Nias ethic, which became an event and was a grafting of a name from a cultural perspective to a theological one. This is related to the name of God from Deitas Lowalangi which is one of the names of ethical figures on the island of Nias who is used as a synonym for the name of God. If you look at it, there are actually many other name deities that are choices for God's name. And this is the topic of discussion in this article and its application to the lives of the people of Nias today. This research was carried out by means of literature studies and interviews with several Nias ethnic figures who were sources, both intellectuals and traditional figures and servants of God. The aim of writing this article is that the essence of the name Lowalangi is not just changing the name to God but has a deep meaning without any interference from the name of the god worshiped by the Nias ethnic group, as well as strengthening the faith of the Nias Christian people in actualizing the name of God in religious and cultural life. Through understanding the name of God from the Nias ethnic perspective, that the true name of God is implemented correctly and on a Biblical basis. The connection between the name of God in the Nias ethnic group is only limited to the name adopted by missionaries to straighten out the faith of Christians on Nias Island. Because no other Lowalangi name is misused by Christians in any worship. Because what must be worshiped is the real Lowalangi in the Bible, not Lowalangi because it is based on the name of a traditional figure, god or ancestor.